2018
DOI: 10.1002/ccd.27725
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocardial infarction secondary to blunt chest trauma in motorcycle accident: A rare combination where percutaneous coronary intervention and intravascular imaging optimization are needed

Abstract: Blunt chest trauma is a common occurrence in vehicle accident. Cardiac injuries following nonpenetrating thoracic trauma have been reported. ST-elevation myocardial infarction (STEMI) due to coronary artery involvement is a rare but extremely serious condition for the high risk of undetected diagnosis. Blunt thoracic trauma may obscure typical chest pain associated with cardiac ischemia especially in patients with high tolerance of pain or secondary administration of analgesic drugs. We report two consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…12,13 Poor lifestyle, stress, anxiety, and depression are risk factors for the recurrence of coronary heart disease. 14,15 To mitigate the anxiety and depression of postoperative patients with PCI after discharge and to improve their quality of life, we used WeChat to carry out remote health management. In this study, we analyzed the effect of implementing remote health management for patients after PCI in our hospital on reducing their anxiety and depression and enhancing their quality of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Poor lifestyle, stress, anxiety, and depression are risk factors for the recurrence of coronary heart disease. 14,15 To mitigate the anxiety and depression of postoperative patients with PCI after discharge and to improve their quality of life, we used WeChat to carry out remote health management. In this study, we analyzed the effect of implementing remote health management for patients after PCI in our hospital on reducing their anxiety and depression and enhancing their quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the pain associated with the disease, the risk of recurrence, the need for long-term standardized medication and a good lifestyle, and the sudden lack of medical care after discharge, post-PCI patients generally face greater stress after discharge, with anxiety, depression, and low quality of life 12,13. Poor lifestyle, stress, anxiety, and depression are risk factors for the recurrence of coronary heart disease 14,15…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, taking effective first-aid measures is an important means to save the lives of patients. Clinical studies have confirmed that previous medical history, dyslipidemia, smoking, obesity, emotional agitation, and so on are all risk factors for AMI [ 3 5 ]. The development and application of percutaneous coronary intervention (PCI) have significantly improved the prognosis of AMI patients, and PCI has become one of the current clinical methods for the treatment of AMI.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking, a family history of coronary artery disease (CAD), and male sex appear to be the most important risk factors associated with developing a heart attack in this population [3]. Though the most common underlying pathophysiology is related to atherosclerosis and plaque disruption, any obstruction to the blood flow in the coronary arteries could potentially lead to an MI [4][5] The ST-elevation myocardial infarction (STEMI) due to coronary artery damage is a rare but potential complication of blunt chest trauma (BCT) [6][7]. Multiple case reports have described damage to the left anterior descending artery (LAD), which may be due to its proximity to the chest wall [8].…”
Section: Introductionmentioning
confidence: 99%